The Difficulties that Face Sudanese University Students in Speaking English Language. - Dr. Ali Fadlalla Ahmad AL Basheer; د. حسن محمد عبد العال المكاشقي (White Nile Journal for Studies and Research, 2025)
This study aimed at investigating the problems of speaking English skills among Sudanese university students. The study adopted the descriptive analytical method to analyze the data. The researchers used a questionnaire for collecting data. Twenty-five students were chosen to represent the sample of population of this study. The study tackles the problems that face Sudanese university students when they speak English. The main factors that caused this problem either, psychologically or, linguistically. The study has some findings, the most important ones are: Teachers and students do not pay considerable attention for creating a new style to teach and learn speaking English skills. In addition, teachers do not motivate students to speak English appropriately. The study concluded with some recommendations, one of them is that, practicing speaking English can help students to master speaking skill effectively.